Nutritional supplementation and resistance exercise: What is the evidence for enhanced skeletal muscle hypertrophy? - Gibala, M. J. (Canadian Journal of Applied Physiology, 2000)
Many athletes and recreational weightlifters believe that dietary manipulations ''Ñeither following a single bout of resistance exercise or during habitual training" may augment the normal gains in muscle fibre hypertrophy. Very few studies, however, have directly examined the effect of nutritional supplementation on muscle protein metabolism after resistance exercise. Ingestion of an amino acid and/or carbohydrate solution during the initial hours following a single bout of resistance exercise promotes an acute increase in protein net balance compared to the fasted state. The precise mechanism involved has not been elucidated but seems related to an increased availability of intracellular amino acids and/or an increase in plasma insulin concentration. As a practical recommendation, therefore, postexercise feeding appears to be very important. Recent evidence suggests that creatine supplementation in conjunction with resistance training may elicit larger increases in muscle fibre cross-sectional area compared to training alone. This intervention may be most beneficial in persons with "compromised" skeletal muscle.